Strategies and challenges of parents in managing behaviors of children with special needs undergoing therapy - Fariñas, Maria Ruby P.; Saamong, Charla Rochelle S. (Quezon City College of Home Economics, University of the Philippines Diliman, 2021)
According to national data, one out of seven or around 5.1 million Filipino children are living with disabilities (PhilHealth, 2018) and one in every five persons with disabilities is a child aged 0-14 (Philippine Statistics Authority, 2010). Given the increasing number of families who have children with special needs in the country, this phenomenon is necessary to be looked deeper into to provide more data that may be beneficial in addressing their concerns such as parental attention, family adjustment, services, social supports, and special health care interventions. This study generally aimed to describe the experiences in parenting children with special needs with regard to managing behaviors in relation to therapy services received and identify the evident challenges and strategies that were practiced. Eighteen (18) parent cases who have children with special needs in the areas of Laguna and Cavite participated in an online in-depth interview. The study revealed processes that parents went through when they found out about their child's condition, namely: (1) observation, (2) consultation and diagnosis, and (3) intervention. Each process had its own challenges that parents needed to address through formulation of strategies suited for their needs as well as usage of available resources. Challenges encountered by parents along their journey were: (1) delays in development milestones, (2) difficulties in obtaining slots for services - doctor's appointment and/or therapy schedules, (3) limited awareness of child's condition and therapy services, (4) child care demands, (5) financial demands of intervention services, (6) social stigma, and (7) strains in family relationships. Moreover, as parents gained knowledge and skills with the support of internal and external resources, they were able to develop strategies to address the identified challenges such as: (1) asking/finding doctors, (2) further observation, (3) researching through the internet, (4) finding other doctors and/or therapy centers, (5) observation and partnership with therapists, (6) adjustment in family functioning, and (7) raising awareness. Given the importance of therapy in their children's lives as majority of the parent respondents have accounted, intervention has not only developmentally affected children with special needs, but has also personally influenced the parents of their own growth. As a conclusion, parents' personal experiences revealed constant processing of input to their system brought about by having children with special needs thus requiring persisten adjustment by all members to obtain optimal family functioning on a daily basis. Based on the results, it is highly recommended to provide centralized services and alternative approaches to intervention such as online therapy to strengthen the overall support for PWDs and their families with regard to access to information, health and therapy services, educational programs, livelihood, and employmen
Thesis Classification
Thesis
Includes bibliographical references and appendice
Keywords: Children with disabilities -- Psychology; Children with disabilities -- Care -- Philippine; Parents of children with disabilities -- Philippines; Child psychology